Editorial to the Proceedings of the TensiNet - COST Action TU1303 Symposium 2016. (2016) - Chilton, John; Gosling, Peter; Mollaert, Marijke; Stimpfle, Bernd
Abstract: The TensiNet Association, in collaboration with the COST Action TU1303 "Novel structural skins: Improving sustainability and efficiency through new structural textile materials and designs" and the Newcastle University organized the TensiNet - COST Action TU1303 Symposium 2016 held in Newcastle upon Tyne, UK, from Wednesday 26 th to Friday 28 th October 2016. This paper presents the 3-day event introducing the topics selected for the sessions, the keynote lectures and speakers and the sponsors which supported the organization of the symposium.